INTERRELATIONSHIP BETWEEN DIABETIC FOOT SYNDROME AND CORONARY ARTERY DISEASE - Kamalov, S.T. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background: Diabetic foot syndrome (DFS) and coronary artery disease (CAD) are two of the most devastating complications of type 2 diabetes mellitus (T2DM), frequently coexisting and interacting through overlapping vascular, metabolic, and inflammatory pathways. Understanding their pathophysiological interdependence is essential for effective management of high-risk diabetic populations. Methods: This narrative review synthesizes current literature on shared mechanisms linking DFS and CAD, including endothelial dysfunction, atherogenesis, systemic inflammation, and impaired microcirculation. Emphasis is placed on epidemiological data, cardiovascular risk stratification, and clinical outcomes in patients with combined DFS and CAD. Results: T2DM accelerates atherosclerosis and promotes multivessel coronary involvement, while also contributing to peripheral ischemia and neuropathy characteristic of DFS. Chronic hyperglycemia, oxidative stress, dyslipidemia, and platelet hyperreactivity play central roles in both coronary and peripheral artery disease. Patients with both conditions exhibit significantly higher rates of amputation, cardiac events, and mortality, underscoring the need for integrative management approaches. Conclusion: DFS and CAD share a common pathophysiological foundation and should be regarded as manifestations of systemic diabetic angiopathy. Risk prediction and treatment strategies must account for the bidirectional impact of these conditions. Early cardiovascular screening in DFS patients and individualized vascular intervention planning are essential to improve limb and life prognosis.